COMMUNITY EMPOWERMENT ON INFRASTRUCTURE DEVELOPMENT IN KABANGKA VILLAGE MUNA REGENCY - La Welendo; Edward Ngii; Adris Ade Putra; Siti Nurjanah Ahmad; Waode Sitti Warsita Mahapati (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2023)
Community service is a form of higher education tri dharma, namely a team of lecturers from the Faculty of Engineering, Halu Oleo University which was held in Kabangka village, Muna Regency. Kabangka Village is a potential area and sufficient natural resources, in this case the spring tourism potential (Fotuno Sangia) which is often visited by local and even foreign tourists, agricultural land is very fertile, but road access to the village needs serious attention from all parties. . Community service aims to contribute in the form of knowledge about infrastructure development to improve the welfare of the community in Kabangka Village, Muna Regency. The process of implementing this service is a technique of implementing infrastructure and outreach to the farming community and the local village government. The Community Partnership Program is carried out by involving the community in the kabangka village of Muna Regency. The methods used in community service are sample provide, direct and face-to-face discussions with the community, and field applications in infrastructure development oriented to improving village roads. The results of the implementation of community service contribute to product work on infrastructure development, especially the improvement of village roads as access to community mobility movements to support economic, social, educational, and other activities. The community has a fairly good response and high enthusiasm for the program carried out by the lecturer team.Â Â